Effect of ultrasound-assisted cold plasma pretreatment to obtain sea asparagus extract and its application in Italian salami. (November 2020) - Faria, G.Y.Y.; Souza, M.M.; Oliveira, J.R.M.; Costa, C.S.B.; Collares, M.P.; Prentice, C.
Graphical abstract: Highlights: Cold plasma pretreatment enhanced the antioxidant activity of S. neei extract. Plasma etching effect was observed in the plant surface morphology. S. neei extract displayed low antimicrobial activity against E. coli. Dry fermented sausages (Italian salami) were produced using S. neei extract. S. neei extract partially replaced nitrite without major impact on salami. Abstract: The effect of the glow discharge cold plasma pretreatment (CPT) was investigated on the ultrasound-assisted extraction (UAE) of phenolic compounds from sea asparagus Salicornia neei. The extract was applied in dry fermented sausage (Italian salami). Thermal extraction methods demand a long processing time, are highly energy-consuming and cause irreversible nutrient losses. It was found that CPT (discharge power of 14 W for 5 min) prior to UAE increased the antioxidant activity by 22% and 19% measured by the DPPH and ABTS assays, respectively. The S. neei extract showed high antioxidant activity, low antimicrobial activity, and was added to salami formulations with reduced-sodium nitrite content and no addition of sodium erythorbate. Despite a slight color change, lipid oxidation and texture parameters were similar to the control at the end of ripening. Furthermore, higher antioxidant activity was observed in S. neei extract supplemented salami with no impact on its sensory overall acceptability, indicating its potential as a natural alternative to synthetic additives.